Management of a Type Ia Endoleak With the Nellix Endovascular Aneurysm Sealing System. (June 2015) - Hughes, Cían O.; de Bruin, Jorg L.; Karthikesalingam, Alan; Holt, Peter J.; Loftus, Ian M.; Thompson, Matt M.
Purpose: To report the application of the Nellix endovascular aneurysm sealing (EVAS) device, including two chimney grafts, to successfully treat a type Ia endoleak.Case Report: An 87-year-old man had an asymptomatic 7.6-cm infrarenal abdominal aortic aneurysm (AAA) and a 4.5-cm right internal iliac artery aneurysm treated using an aortouni-iliac stent-graft. Two years after the index endovascular repair, an asymptomatic type Ia endoleak was detected on duplex ultrasound; the computed tomographic angiogram (CTA) demonstrated significant sac enlargement and stent-graft migration. Initial attempts to treat the leak with 2 aortic cuffs only reduced the size of the endoleak. Another procedure was undertaken using the Nellix device with chimney grafts to increase the proximal sealing zone above the existing stent-graft. Imaging postoperatively demonstrated successful resolution of the endoleak and continuing patency of both renal artery chimney stent-grafts. CTA at 6 months demonstrated persistent sealing of the endoleak.Conclusion: The use of the EVAS system may represent another endovascular solution that can be added to the clinician's repertoire for treating type Ia endoleak after conventional endovascular repair of infrarenal AAA.